Ameliorative effects of crocin on paraquat-induced oxidative stress in testis of adult mice: An experimental study - Fahime Sadat Kamali; Rasoul Shahrooz; Golamreza Najafi; Mazdak Razi (Shahid Sadoughi University of Medical Sciences, 2019)
Background Paraquat (PQ), as a pyridine compound, is widely used worldwide to control annual weeds. The oxidative stress caused by PQ can cause deleterious changes in the testicular tissue. Objective An investigation on the protective effects of Crocin (CCN) against PQ-induced oxidative damages and apoptotic indices in testicular tissue. Materials and Methods Twenty-eight adult male albino mice (20-25 gr) were divided into four groups (n = 7/each). The control group received 0.1 ml/day of normal saline by intraperitoneal injection (IP); sham-control group received PQ 5 mg/kg/day, IP, and the experimental groups received PQ (CCN+PQ) and CCN-sole (200 mg/kg/day, IP), respectively, for 35 continuous days. At the end of the treatment period, the testes were dissected out and used for biochemical, molecular, and histological analyses. The expressions of tumor suppressor p53, B-cell lymphoma 2 (bcl-2), and caspase-3 were considered as hallmark factors of mitochondria-dependent apoptosis. Moreover, the testicular superoxide dismutase (SOD) and malondialdehyde (MDA) were evaluated as key biomarkers for oxidative stress. Results The PQ significantly (p < 0.02, p < 0.01) diminished the spermatogenesis indices and SOD, increased MDA levels, and enhanced the apoptosis-related gene expression. However, the co-administration of CCN and PQ significantly (p < 0.01, p < 0.01, p < 0.02) ameliorated the spermatogenesis ratio, upregulated the SOD level as well as bcl-2 expression, and reduced the MDA content and apoptosis vs the PQ-sole group. Conclusion This study showed that the antioxidant properties of CCN enable to ameliorate the PQ-induced destructive effects by upregulating the testicular structure, antioxidant and apoptotic status.